Neonatal pertusis with classical whoop: an unusual scenario - Joshi, Payas; Bhatia, Sumit; Kishore, Jay; Jhaz, Chetnanand (International Journal of Contemporary Pediatrics, 2018)
Pertusis affects all the age groups but is most severe in neonates and early infancy and may even cause mortality. Clinical presentation of neonatal pertusis is varied and thus knowing the spectrum of clinical presentation is vital for early diagnosis. Unlike older children, most of the times neonatal pertusis has an atypical presentation and classical presentation is very rare. Here we present such a rare case of neonatal pertusis who presented with classical symptoms of pertusis.